1965
DOI: 10.1177/00220345650440012201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of X-Chromosome Aneuploidy on Jaw Growth

Abstract: It is now increasingly evident that chromosomal abnormalities underlie a goodly proportion of congenital abnormalities, between 5 and 15 per cent of children with congenital abnormalities showing evidence of chromosomal deletions or aberrations. Since dentofacial defects are particularly common in developmental abnormalities, and to an extent not in accordance with the concept of stage-specificity, the possible chromosomal basis of dentofacial defects represents a problem in its own right and, when the chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
1

Year Published

1978
1978
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 51 publications
(11 reference statements)
1
20
1
Order By: Relevance
“…In the present case, four permanent teeth were absent. As described by some authors 13,18 that the patients with KS have mental retardation as in this patient. Most of the authors described prognatism about the jaws but only a large maxiller arch was seen in this patient.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…In the present case, four permanent teeth were absent. As described by some authors 13,18 that the patients with KS have mental retardation as in this patient. Most of the authors described prognatism about the jaws but only a large maxiller arch was seen in this patient.…”
supporting
confidence: 65%
“…2,6, 13 The characteristic clinical findings of this syndrome may vary but most of the patients have infertility, tall, slender body habitus with long legs and shorter torso, a coarse face, skeletal anomalies, hypogonadism, osteoporosis, mental retardation, aspermatogenesis, variable gynecomastia, small testis and penis. In addition to these findings, language delays, learning problems, behavioral difficulties and cardiovascular problems may occur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult stature is typically very short, mean height being about 140 cm, and birth weight also tends to be below average (Hamerton, 1971). Furthermore, craniofacial morphology is altered, with facial retrognathism and flattening of the cranial base (Gorlin et al, 1965;Filipsson et al, 1965). XO individuals also tend to show retardation in skeletal maturation (Tanner et al, 1959;Park et al, 1983).…”
mentioning
confidence: 99%
“…According to them, Klinefelter patients showed increased mandibular prognathism together with increased maxillary prognathism, which could be related to the altered shape of the cranial base rather than the altered size and position ofthe jaws. Also, Gorlin et al (1965) have suggested that the loss or addition of an X chromosome …”
Section: Discussionmentioning
confidence: 99%